GAMBARAN KETEPATAN PERSONIL PENDAMPING DAN AMBULANS YANG DIGUNAKAN DALAM MERUJUK PASIEN GAWAT DARURAT DI INSTALASI GAWAT DARURAT RSUP PROF DR. R. D. KANDOU MANADO - Montjai, Stevi; Mulyadi, Ns; Lolong, Jill (JURNAL KEPERAWATAN, 2017)
Abstract : Transporting emergency patients with critical condition is susceptible to risks such as, delayed handling and management of patients that could result in deaths. Hence, management and transportation or patient referring should be taken as a priority. Transporting or referring emergency patients requires emergency ambulance that provided with emergency equipment, and it needs doctors and nurses experienced in emergency medicine. Currently not optimal process of transporting and referring patients is due to lack of transportation and also the use of two-wheeled vehicles. The aim of this research is to find the overview of proper escorting personnel and ambulances that used in referring emergency patients. The samples that we used are 80 patients that obtained by using purposive sampling method. The method used in this study is descriptive survey and the data were collected by using observation sheets. Conclusion: We found that in most cases of patient referring, escorting personnel are dominated by nurses and emergency staffs. The uses of ambulances on referring patients are dominated by emergency ambulances. Keyword : Patient referring, Emergency, Ambulance, Escorting personnel Abstrak : Transport pasien dalam keadaan kritis mempunyai resiko pada pasien gawat darurat, keterlambatan penanganan dapat berakibat kematian, untuk itu penting memprioritaskan penangangan dan transport atau rujukan bagi pasien. Transport atau merujuk pasien gawat darurat memerlukan ambulans gawat darurat yang dilengkapi dengan perlengkapan penanganan kegawat daruratan serta memerlukan penanganan dari dokter dan perawat berkemampuan penanganan gawat darurat. Belum optimalnya proses rujukan pasien gawat darurat karena terkendala sarana transportasi serta masih ditemukannya penggunaan kendaraan roda dua dalam merujuk pasien. Tujuan Penelitian ini untuk mengetahui gambaran ketepatan personil pendamping dan ambulans yang digunakan dalam merujuk pasien gawat darurat. Sampel berjumlah 80 pasien yang didapatkan dengan teknik Purposive Sampling. Desain Penelitian survei deskriptif dan data dikumpulkan menggunakan lembar observasi. Kesimpulan gambaran merujuk pasien dengan personil pendamping didominasi oleh perawat dan pekarya. Sedangkan penggunaan ambulans saat merujuk pasien, didominasi oleh ambulans gawat darurat. Kata Kunci : Merujuk Pasien, Gawat Darurat, Ambulans, Personil Pendamping